Barriers to seeking care for memory problems: A vignette study. Issue 1 (14th March 2022) - Jacobson, Mireille; Joe, Elizabeth; Zissimopoulos, Julie
Abstract: Introduction: This study compares how older adults judge the need for follow‐up care for memory‐related problems when they are responding about themselves versus someone of the same age. Methods: Adults ages 65 and over in the Understanding America Study, a nationally representative internet panel, were invited to participate in a short survey with three vignettes describing memory‐related problems associated with normal aging, mild cognitive impairment, and mild dementia. Respondents were randomly assigned to vignettes about themselves or about an individual of the same age and asked whether the problems warranted follow‐up discussion with a health‐care provider. Unadjusted and covariate‐adjusted differences in the percent of affirmative responses to follow‐up discussion and an index, ranging from 0 to 3, that summed affirmative responses, were compared across respondents randomly assigned to self‐ versus other‐framed vignettes. Results: One thousand six hundred twenty‐eight panel members (81.6%) completed the survey (mean age, 72.3 [range, 65–102], 801 female [49.2%] and 827 male [50.8%]) with 796 (48.9%) randomly assigned to vignettes about themselves and 832 (51.1%) to vignettes about individuals of the same age. Percent affirming need for follow‐up ranged from 66.9% to 90.5% and was systematically lower for those randomized to vignettes about themselves. The differences ranged from –10.8 percentage points (95% confidence interval [CI], –13.6 to –7.9 percentage points) for the most severe to –13.9 percentage points (95% CI, ‐18.1 to –9.7 percentage points) for the mildest memory‐related problem vignettes. The summary index was –0.444 points (95% CI, 0.563 to –0.326) or 0.491 of a standard deviation (95% CI, 0.622σ to ‐0.362σ) lower for scenarios about participants themselves relative to others. Discussion: Seniors were more likely to recognize and recommend follow‐up for memory‐related problems affecting someone else than the same problems affecting themselves, suggesting symptom education alone may not improve rates of cognitive assessment for detection of impairment and dementia.